Accessibility of expressed and non-expressed genes to a restriction nuclease. - Pfeiffer, W (1980)
Nuclei of mouse liver and an immunoglobulin producing myeloma were digested with HaeIII or its isoschizomer BspRI. The DNA fragment patterns after electrophoresis, blotting, and hybridization were very similar for the two types of nuclei when a probe for the non-expressed beta-globin gene was used. The constant (C) region of the kappa light chain gene, on the other hand, was more accessible to the nuclease in myeloma than on liver nuclei. In myeloma nuclei the BspRI sites were about equally sensitive, in fact the pattern resembled a partial digestion pattern of free DNA. In contrast, in liver nuclei some sites were much more protected than others. This is interpreted by assuming that this single copy non-expressed gene region is covered by nucleosomes which are preferentially located on certain DNA sequences. Restriction nuclease digestion of nuclei seems to be a promising method for the analysis of genes in their expressed and non-expressed states.